Kitab Suci, Bahasa Arab dan Pembacaan Teks: Tinjauan Filsafat Mohammed Arkoun - Ismail Suardi Wekke (Universitas Islam Negeri Mataram, 2014)
Mohammed Arkoun is one of the great contemporary Muslim thinkers who advocate reforms of Islamic thought. This study seeks to explore Arkoun’s thoughts on The Book, Arabic language and reading scriptural text. Arkoun argues that when Muslims read the Qur’an as it is historically revealed, they will recreate Islam only as a dogma. Furthermore, he argues that it is a mandatory to rethink Islam from socio-cultural perspectives. The legacy of Islamic thoughts is accepted but it is also needed to be re-actualized because it was formulated in the specific time and place in the past. As for Arabic language, Arkoun thinks that as the language of the Qur’an, Arabic must become open language to any socio-cultural changes. However, since its enclosure as the unified codification, the Qur’an becomes “a close corpus”, which renders reinterpretation difficult. To solve this problem, he promotes the idea of de-construction of reading sacred text.